Modelo de participación de enfermería en promoción de la salud y prevención de la enfermedad (2000)
ABSTRACT: This article shows the nursing involvement in health promotion and disease prevention, based on the epidemiological surveillance or the strategic monitoring used by social epidemiology. In this way, outstanding interventions is established in reducing unnecessary morbidity and mortality and in keeping life quality according to human dignity in order to bring well-being and self-management. The analysis with competence of the determiners of the health-disease process of people, families and collectives is compulsory to plan and evaluate the projects presented in health. Thus, three phases are stated, in which the participation, monitoring and decision making are coherent and base on real social contexts deserving intersector and interdisciplinary participation.